Utility of dried blood spot sampling and storage for increased stability of photosensitive compounds. (November 2010) - Bowen, Chester L; Hemberger, Matthew D; Kehler, Jonathan R; Evans, Christopher A
Background: Compound stability remains a major point of concern within pharmaceutical development. In attempts to minimize degradation, scientists may utilize acidification of samples prior to storage, dark chambers, decreased freezer temperatures and a variety of other stabilization techniques. All of these steps require additional procedures, increased costs and increased validation steps. Dried blood spots (DBS) are becoming a popular alternative to plasma sampling in many small- and even large-molecule applications. An investigation was performed in order to establish if DBS would provide storage advantages over liquid-based matrices for two light-sensitive compounds, nifedipine and omeprazole, to prevent or minimize photodegradation.Results: Experimental data has shown, through forced and natural photodegradation experiments, that the compounds nifedipine and omeprazole exhibit increased photostability when spotted and stored on various DBS paper, when compared with water, plasma or whole blood. For omeprazole, between 40 and 90% loss was observed in liquid matrices, while photodegradation was negligible when utilizing DBS. Some loss of nifedipine is noted during exposure conditions on DBS; however, photodegradation in liquid matrices is far more severe.Conclusion: Within the experimental compound set, DBS technology offers a significant reduction in the photodegradation process when compared with the liquid matrices water, plasma or blood.